Metabolizable Energy Requirements for Broiler Breeder in Different Environmental Temperatures - Reyes, M.E.; Salas, C.; Coon , C.N. (International Journal of Poultry Science, 2012)
A 10 wk feeding experiment was conducted to develop a model for predicting the ME requirement for broiler breeder hens housed in different environmental temperatures. Three groups of 50 Cobb 500 broiler breeder hens were individually housed in breeder cages located in environmentally controlled rooms set at 15.5, 23 and 30°C. Each breeder was given an intramuscular injection of Tamoxifen (TAM) (5 mg/kg BW) in corn oil at days 1 and 4 to stop egg production. Ten breeders from each environmental temperature were sacrificed for carcass composition analysis at the beginning of the study. Breeders, during the non-laying period, housed at 15.5°C were fed 100 g providing 285 kcal MEn/b/d (2851 kcal/kg; 16%CP) and breeders housed at 23°C and 30°C were fed 93 g providing 265 kcal MEn/b/d of same diet. Five breeders were sacrificed from each environmental room after the breeders resumed egg production. The ME requirement for maintenance (MEm) determined during the non-laying period was 104.3, 98.1 and 99.4 kcal/kg0.75 for birds housed in 15.5, 23 and 30°C, respectively. At first egg, 136, 130 and 128 g/bird/d of same diet previously fed during the non-laying period provided 388, 371 and 365 kcal MEn/b/d to broiler breeder hens housed at 15.5, 23 and 30°C, respectively. The egg number, egg weight and BW change for each breeder during egg production was evaluated through the remainder of the 10 wk period. At the end of the trial, all birds were sacrificed and frozen at -4°C for carcass composition analysis. Body weight data collected during the non-laying period was used to construct a single equation by plotting Metabolizable Energy (ME) against body weight change (BWΔ) for each individual hen to calculate the MEm. Egg production and egg weights were recorded daily after egg production resumed. The MEg and MEe requirement for BW gain and egg production were determined for breeders in each of the environmental temperatures based on the energy content of carcass and egg mass and the respective efficiency of energy utilization. The average MEg and MEe for the three environmental temperatures was 5.8 kcal/g and 2.3 kcal/g, respectively. Three equations were developed from the feeding experiment to predict ME needs for breeders: Eq. 1: (ME = BW0.75 [111.9 - 0.46 T] + 5.8G + 2.3EM); Eq. 2: (ME = BW0.75 [110.3 - 0.47 T + 0.055 (T - 22.5)2] + 5.8G + 2.3EM); Eq. 3: (ME = BW0.75 [111.02 - 0.49 T + 0.049 (T - 22.07)2] + BWΔ (1/0.77 x ERf + 1/0.37 x ERp) + ECE/0.73 x EM), where ME = Metabolizable Energy (kcal), BW = Body Weight (kg0.75), T = Temperature (°C), BWΔ = Body Weight change (g/d), ERf = Energy Retained as fat (kcal), ERp = Energy Retained as protein (kcal); ECE = Energy Content of Eggs (kcal/g) and EM = Egg Mass (g).